1993
DOI: 10.1128/jcm.31.8.2061-2065.1993
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycobacterium species by using amplified ribosomal DNA restriction analysis

Abstract: A rapid procedure for the identification of cultured Mycobacterium isolates, based on the combination of enzymatic amplification and restriction analysis, is described. The 16S rRNA genes (rDNA) of 99 strains belonging to 18 different species of the genus Mycobacterium were enzymatically amplified. Amplified rDNA restriction analysis with the enzymes CfoI, MboI, and RsaI was carried out. The combination of the amplified rDNA restriction analysis patterns obtained after restriction with CfoI and MboI enabled di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 24 publications
1
59
1
3
Order By: Relevance
“…ARDRA was previously shown to be useful for typing (10,26). However, our study revealed a low DI (0.743) when this technique was applied to the 16S-23S rRNA spacer region of gonococci.…”
Section: Discussioncontrasting
confidence: 56%
“…ARDRA was previously shown to be useful for typing (10,26). However, our study revealed a low DI (0.743) when this technique was applied to the 16S-23S rRNA spacer region of gonococci.…”
Section: Discussioncontrasting
confidence: 56%
“…We did set up efficient bacterial genomic DNA extraction techniques from stools to amplify 16S rDNA from all samples using selected universal primers. We initially used ten different restriction enzymes that were indicated as diagnostic [21,22] to digest one sample of amplification pool of bacterial 16S rDNA according to the method of Vaneechoutte et al [23]. The pools of digested DNA were analyzed and, based on the results, we selected four 4 bp restriction enzymes (HaeIII, AluI, MspI, RsaI-Fermentas, Cornaredo, Milan, Italy) that generated more diagnostic restriction profiles, producing the greatest number of restriction fragments in our samples ( Fig.…”
Section: Ardra Techniquementioning
confidence: 99%
“…Until now, the presence of one copy of the 16S rRNA gene has been described only for slow-growing mycobacteria [31]. Rapid identification of mycobacterial species has been developed using restriction enzyme analysis of PCR-amplified fragments of highly 23 conserved genes [33,34], but both studies have been mainly applied to slow-growing mycobacterial species.…”
Section: Kbpmentioning
confidence: 99%